THE RELATIONSHIP BETWEEN SOCIAL CAPITAL AND ECONOMIC BEHAVIOR PATTERNS OF GRADUATES - A. A. Avakian (Дискурс)
The article considers the relationship between social capital and economic behavior patterns of university graduates. The concept of social capital is defined. Sociological approach provides an opportunity to evaluate the essential role of social capital in the system of multilateral social relations. The article presents the results of an empirical study of economic behavior of university graduates that form social capital, regulating economic behavior in regard to income accumulation, consumption and generation. It is revealed that successful adaptation of graduates in the labor market, which is an important part of their social development and active economic behavior, depends on many factors. Their influence provides a particular result in the course of professional self-realization, particularly on social capital. Social capital is considered at the micro level: relationships within a family, among relatives, friends and acquaintances. The study shows a significant impact of university graduates social capital on forming active economic behavior.